Role of plasma neuropeptide Y in acute myocardial infarction: a case-control study - Yan-li Zheng; Hui-li Lin; Yue-ting Li; Mei-mei Li; Jing-ru Du; Wan-da Wang; Yao-guo Wang; Yin-lian Cai (BMC Cardiovascular Disorders)
Abstract Background As neuropeptide Y is associated with endothelial dysfunction, this study explored the relationship between neuropeptide Y and acute myocardial infarction. Methods We included 128 acute myocardial infarction cases and 62 controls. Using the SYNTAX scoring system, the acute myocardial infarction group was sub-grouped into “SYNTAX ≤ 22,” “SYNTAX = 23–32,” and “SYNTAX ≥ 33.” Plasma neuropeptide Y, endothelin, endothelial nitric oxide synthase, and thromboxane A2 levels were measured. Results The acute myocardial infarction group had higher plasma neuropeptide Y, endothelin, and thromboxane A2 levels than controls ([58.76 ± 17.63 vs. 37.48 ± 11.36 ng/ml, P = 0.000], [36.16 ± 10.04 vs. 27.80 ± 7.18 pg/ml, P = 0.000], and [27.69 ± 6.91 vs. 24.32 ± 7.28 pg/ml, P = 0.002], respectively). The acute myocardial infarction group also had lower plasma endothelial nitric oxide synthase levels than controls (3.00 ± 0.94 vs. 4.05 ± 1.44 ng/ml, P = 0.000). Additionally, the receiver operating characteristic curve analysis showed that a neuropeptide Y value of 49.94 ng/ml could help diagnose acute myocardial infarction (sensitivity: 70.9%; specificity: 91.9%). The SYNTAX scores, smoking, plasma endothelin, thromboxane A2, and neuropeptide Y levels were positively correlated, whereas plasma endothelial nitric oxide synthase and neuropeptide Y levels were negatively correlated. Lastly, plasma neuropeptide Y levels were different among subgroups (P < 0.05); patients with higher SYNTAX scores had higher neuropeptide Y levels. Conclusions The levels of plasma NPY may be accociated with the AMI process.